Peran IPS dalam Pendidikan Multikultural di Indonesia - Putranto, Anggoro (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2017)
The problem in this country would have an impact on social life. Most of a person likely to take care of somebody else's problem than the problem itself. Differences in beliefs and fellow beliefs often form groups or class, so it tends to far from each other. Education social sciences play a role in promoting a peaceful life, to encourage a person to improve adaptation to each other, can improve better communication and improve one's relationship. Education social sciences to integrate various disciplines such as geography, history, sociology, economics and anthropology community. IPS implementation of learning emphasis is on the field of education, thus gaining additional knowledge on the attitudes and behaviors, values, and of good character and can play a role in people's lives and can inculcate a scientific attitude in order to solve the problems faced around. The integration of learning social studies from various disciplines social imu can be done based on a specific topic that is still associated with other disciplines. Multicultural education as a strategy to take advantage of the various cultures of different communities of students is unique or typical of students to form a multicultural attitude of mutual understanding and mutual respect so as to create a tolerant education sector. IPS study integration of education in multicultural education can contribute realize strong society in the development of globalization and uphold the basic philosophy states that diversity, make education more increased quality and more advanced.